Militarization, stigma, and resistance: negotiating military reservist identity in the civilian workplace. Issue 2 (3rd April 2021) - Higate, Paul; Dawes, Antonia; Edmunds, Tim; Jenkings, K. Neil; Woodward, Rachel
ABSTRACT: Set against the backdrop of the British Government's Future Reserves 2020 (FR2020) programme, this article addresses military reservists' experiences of how they are perceived by civilian colleagues in the workplace. Drawing on qualitative interviews with reservists, it analyses their understandings of civilian co-workers' qualified and sometimes reluctant acceptance in light of FR2020's implicit aim to use reservists to help realign civil–military relationships. While it appears that civilian work colleagues' social distancing of reservists helps consolidate the wider public's perceived lack of understanding of the British armed forces, a more critical view sees reservists' largely unchallenged presence in the workplace as an exemplary, yet subtle instance of militarization. This is because reservists' simultaneous (physical) inclusion and (social) distancing or stigmatization constitutes, and is constitutive of, their need to pass as civilian. In conclusion, we argue that a key implication of their passing as civilian is to neutralize debate of the legitimacy – or otherwise – of the armed forces as an institution tasked with violence on behalf of the state.